(untitled) (Global Journal of Science Frontier Research, 2020)
The tomato crop is affected by a number of pests in the world as well as in China and Pakistan. The whitefly (Bemisia tabaci) is considered a very serious and damaging pest of tomato crop along with many other vegetables and field crops. Population buildup of whitefly is affected by many factors, including biotic and a biotic. One of the factors affecting the whitefly population in the tomato crop is green peach aphid (Myzus persicae) infestation before the whitefly attack. This project designed to note the direct and indirect effect of Myzus persicae infestation on the population setup of whitefly in tomato crops. The results revealed that whitefly prefers tomato plants without having aphids on them (choice) and can be settled on the tomato plants also when there are aphids present (no choice). The period after aphid infestation have a negative effect on the whitefly population, and the density of aphids/leaf has also influenced the whitefly population.